Developmental Regulation and Induction of Cytochrome P450 2W1, an Enzyme Expressed in Colon Tumors - Choong, Eva (PLoS One, 2015)
Cytochrome P450 2W1 (CYP2W1) is expressed predominantly in colorectal and also in hepatic tumors, whereas the levels are insignificant in the corresponding normal human adult tissues. CYP2W1 has been proposed as an attractive target for colorectal cancer (CRC) therapy by exploiting its ability to activate duocarmycin prodrugs to cytotoxic metabolites. However, its endogenous function, regulation and developmental pattern of expression remain unexplored. Here we report the CYP2W1 developmental expression in the murine and human gastrointestinal tissues. The gene expression in the colon and small intestine commence at early stages of embryonic life and is completely silenced shortly after the birth. Immunohistochemical analysis of human fetal colon revealed that CYP2W1 expression is restricted to the crypt cells. The silencing of CYP2W1 after birth correlates with the increased methylation of CpG-rich regions in both murine and human CYP2W1 genes. Analysis of CYP2W1 expression in the colon adenocarcinoma cell line HCC2998 revealed that the gene expression can be induced by e.g. the antitumor agent imatinib, linoleic acid and its derivatives. The imatinib mediated induction of CYP2W1 suggests an adjuvant therapy to treatment with duocarmycins that thus would involve induction of tumor CYP2W1 levels followed by the CYP2W1 activated duocarmycin prodrugs. Taken together these data strongly support further exploration of CYP2W1 as a specific drug target in CRC.